(untitled) (International Journal of Engineering and Computer Science, 2024)
This study delves into the evolving landscape of gully erosion in South-East Nigeria, conducting a thorough analysis of trends and patterns over the decade from 2010 to 2020. The research unveils significant variations in gully area changes across states, emphasizing the dynamic nature of this environmental challenge. Key findings highlight the severity of gully erosion in Anambra State, with distinct trends and growth patterns identified in each region. The increasing trend in gully areas underscores the urgency for tailored erosion control strategies, while spatial metrics reveal dominant growth types, guiding region-specific interventions. The study’s implications emphasize the need for adaptive management practices and continuous monitoring to address the evolving nature of gully erosion challenges. Overall, this research contributes essential insights for policymakers, researchers, and local communities, informing targeted and effective erosion control measures in South-East Nigeria.